1984
DOI: 10.1016/0378-1135(84)90014-2
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to berne virus in horses and other animals

Abstract: After inoculation into 2 foals, Berne virus induced neutralizing antibody, but did not cause clinical symptoms. In a horizontal study of seropositive mares and their offspring, a decline of maternal antibodies and a sudden synchronous seroconversion in all foals were observed, again without clinical symptoms. The virus is widespread in the Swiss horse population and has been so during the last decade; rises in antibody titers were noted in 9% of paired sera sampled at random. Positive reactions were also obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
52
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 8 publications
(14 reference statements)
4
52
0
Order By: Relevance
“…Antibodies against toroviruses appear to be widespread in ungulates (horses, cattle, sheep, goats and pigs; Weiss et al, 1984;Brown et al, 1987;Koopmans et al, 1989). Some wild mice and laboratory rabbits have also been found seropositive, but inconclusive results were obtained with human sera .…”
Section: History Of Torovirologymentioning
confidence: 99%
“…Antibodies against toroviruses appear to be widespread in ungulates (horses, cattle, sheep, goats and pigs; Weiss et al, 1984;Brown et al, 1987;Koopmans et al, 1989). Some wild mice and laboratory rabbits have also been found seropositive, but inconclusive results were obtained with human sera .…”
Section: History Of Torovirologymentioning
confidence: 99%
“…Epidemiologic studies have shown that BoTV is widespread in the Netherlands [15], Germany and Switzerland [31], the United Kingdom [1], and the United States [29,34], with 55 to 90% of cattle being seropositive. Prospective studies in The Netherlands using an enzyme-linked immunosorbent assay (ELISA) and in Canada using RT-PCR have demonstrated that torovirus was present in 6.4% and 36.4% of calves with diarrhea and in 1.7% and 11.6% of asymptomatic controls, respectively [4,16].…”
mentioning
confidence: 99%
“…Antibodies have also been found in two species of wild mice and in laboratory rabbits [11]. Breda virus can cause life-threatening diarrhea in calves.…”
Section: Epidemiologymentioning
confidence: 93%